2017
DOI: 10.1111/jcc4.12183
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement or Displacement? The Reciprocity of FtF, IM, and SNS Communication and Their Effects on Loneliness and Life Satisfaction

Abstract: Does communication on social network sites (SNSs) or instant messengers (IMsOne often hears that social network sites such as Facebook or Twitter and online instant messengers such as WhatsApp or Snapchat reduce face-to-face communication and make people lonelier and less satisfied with their lives. At the same time, one also hears that these same services instead connect people, foster communication, and increase well-being. In order to further increase our understanding of these phenomena, we asked two quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
122
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(149 citation statements)
references
References 48 publications
9
122
1
1
Order By: Relevance
“…A study of 1 210 Dutch adolescents found that those who spent more time using instant messengers also spend more time in face-to-face interactions (Valkenburg and Peter, 2007). A positive effect of social network use on face-to-face interactions was also found in a longitudinal study using a nationally representative sample of the German population (Dienlin, Masur and Trepte, 2017).…”
Section: Increased Online Interactions Among Friends and Social Networkmentioning
confidence: 90%
See 3 more Smart Citations
“…A study of 1 210 Dutch adolescents found that those who spent more time using instant messengers also spend more time in face-to-face interactions (Valkenburg and Peter, 2007). A positive effect of social network use on face-to-face interactions was also found in a longitudinal study using a nationally representative sample of the German population (Dienlin, Masur and Trepte, 2017).…”
Section: Increased Online Interactions Among Friends and Social Networkmentioning
confidence: 90%
“…9 The two causal pathways identified by the study were, first, a displacement of social activity, with less frequent offline contact and, second, a displacement of strong ties, with strong relationships offline replaced with more superficial ones online. Dienlin, Masur and Trepte (2017) also show that mobile devices have removed pretexts for offline encounters: where people used to meet in person for sharing photos, planning events or gossiping, such functions are now moved to the virtual world.…”
Section: Increased Online Interactions Among Friends and Social Networkmentioning
confidence: 98%
See 2 more Smart Citations
“…In this paper, we define performance as the effectiveness with which people (i.e., athletes) perform activities that contribute to predefined goals and outcomes (i.e., sporting success) [21]. Existing research on the impact of social media on users' performances is two-fold: While a couple of studies have revealed the positive side of social media (e.g., [22,23])for instance, the usage of LinkedIn can result in knowledge sharing and dissemination, or YouTube can be used for training and recruitment [11] social media's negative impact on performance is evident in the majority of studies. These studies commonly report that pervasive social media usage can, for instance, result in technology dependency and excessive usage, which in turn can lead to negative outcomes for users' performances [16,18,24].…”
Section: Linking Social Media and Performancementioning
confidence: 99%